Вплив гідроксикоричних кислот та кумарину на захисні реакції у листках озимої пшениці за дії посухи в ранню фазу онтогенезу - Rositska, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to study the effect of hydroxycinnamic acids and coumarin on physiological and biochemical processes in plants and their role in adaptation to drought. Material and methods. The effect of drought was investigated on plants of Triticum aestivum L. ‘Poliska 90’ growing on 20, 40 and 60 % of soil moisture. The seeds were treated with an aqueous solution of hydroxycinnamic acids (cinnamic, caffeic and chlorogenic acids) and coumarin with a concentration of 10-4 M. To determine the vital state of plants, the content of malonic dialdehyde (MDA), proline, phenolic compounds, proteins, photosynthetic pigments, and catalase activity were studied. Results. The stimulation of plant growth in the experimental conditions of both aboveground and underground parts of plants was revealed. A significant decrease in the content of phenolic compounds in plant leaves in the early stages of ontogeny has been established. In particular, the concentration of flavonoids decreased by 30.8–96.1% relative to control, the content of chlorophyll a and b increased respectively by 2.1–2.6 times and 1.8–2.5 times, the concentration of carotenoids – in 2.0–2.7 times, the protein content – by 17–139 %. There was a direct relationship between the level of supply of plants with moisture and the activity of catalase – with increasing water content in the leaves of plants, the activity of the enzyme decreased, in particular, catalase activity was less than 1.2–1.7 times with respect to control. The concentration of MDA in all variants of the experiment decreased with the increase of the soil moisture. The MDA content decreased by 1.1–2.0 times compared to the control, which indicated the best physiological state of the plants. This is confirmed by a decrease in the concentration of proline in 1.7–12.8 times with respect to control. Conclusion. The treatment of winter wheat seeds with hydroxycinnamic acids and coumarin induces adaptive changes in the leaves, which contribute to increasing the resistance of plants to soil drought.